Metabolomic profiling and identification of potential biomarkers of highly pathogenic avian influenza (H5N1) in chicken - Kadamthodi, Althaf Mohammed; Panwar, Anuradha; Shrungeswara, Akhila Hosur; Vijayakumar, Periyasamy; Prasad, Thottethodi Subrahmanya Keshava; Raut, Ashwin Ashok; Mishra, Anamika (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionHighly Pathogenic Avian Influenza (HPAI) H5N1 is a significant zoonotic pathogen with the potential to cause pandemics. Its high prevalence and mortality rates in poultry, along with a recent expansion in host range, underscore the urgent need to understand the molecular mechanisms underlying its pathogenesis and host-pathogen interactions. Metabolomics, the comprehensive study of small-molecule metabolites within biological systems, offers a promising approach to unravel these mechanisms and aid in the development of effective control strategies against HPAI H5N1.MethodsTo investigate the metabolomic alterations associated with HPAI H5N1 infection, serum and lung samples were collected from specific pathogen-free (SPF) chickens that were either infected with HPAI H5N1 or mock-infected as controls. Metabolomic profiling was performed using liquid chromatography-tandem mass spectrometry (LC-MS/MS) under both positive and negative ionization modes. The resulting data were analyzed to identify metabolites that were significantly altered in response to infection.ResultsThe metabolomic analysis revealed substantial changes in both lung and serum samples following HPAI H5N1 infection. Specifically, 31 and 13 altered metabolites were identified in the lung, and 22 and 15 in the serum, under positive and negative ionization modes, respectively. Notably, key metabolites such as sphingosine, psychosine sulfate, and L-serine, which are known to influence viral endocytosis and cell signaling, were significantly altered in infected chickens.DiscussionThe observed changes in sphingolipid and tryptophan metabolism provide insights into the mechanisms underlying lung and central nervous system (CNS) pathology associated with HPAI H5N1 infection. This study represents the first comprehensive metabolomic profiling of HPAI H5N1-infected chickens, offering valuable information for the development of novel therapeutics and control strategies. The identification of specific metabolite alterations may guide future research aimed at mitigating the impact of this highly pathogenic virus.